Steganalysis tool based on cloud computing / Ahmad A’fif Zulkifli - Zulkifli, Ahmad A’fif (2020)
Steganalysis is the study of discovering hidden data that manipulated by steganography. The goal is to identify the suspected file, determine whether the file have a hidden data encoded and recover the hidden data. Steganography is increasingly being used by criminals creating malware and cyber-attack tools. Forensics examiner may have problems when they want to examine file such as they need to setup the tools itself and the suspected file could be larger than usual. This project aims to develop a steganalysis tool based on cloud to detect hidden evidence for forensic purpose. This project able to detect file with steganography and extract the hidden file. This project can detect image and document files. Project test was carried out to test the functionality of this project. The test involves examining two separate which contain hidden file and the others contain nothing. From this project, it will be able to help forensics examiner to perform steganalysis on cloud. Other than that, this project also will decrease time consuming and computer resources used.